Circuitos mercantis do Porto de Santos às Minas de Goiás entre meados do século XVIII e início do XIX (1765-1808) - Sanches, Thiago [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This research investigates the commercial activity in the captaincy of Goiás in the period of 1765-1808. The main hypothesis is that this activity was intended to ensure the sovereignty and the occupation of the Portuguese Empire in the interior of the continent. To demonstrate this hypothesis will be used the correspondences written by royal officials to the Overseas Council, the bureaucratic documentation of the captaincy published in the collection of DIHCSP, the Board of Finance’s papers of São Paulo’s captaincy, the Ombudsman of Santos’ Royal Treasury and the illustrated dissertations from the time that highlighted the importance of internal trade to the valorization of the inland regions of Brazil’s territory

Esta pesquisa investiga a atividade mercantil na capitania de Goiás no período de 1765-1808. A hipótese central é a de que esta atividade teve como finalidade garantir a ocupação e a soberania do Império português no interior do continente. Para demonstrar essa hipótese, serão utilizadas as correspondências escritas por funcionários régios para o Conselho Ultramarino, a documentação burocrática da capitania publicada na coleção dos DIHCSP, os papéis da Junta da Fazenda da capitania de São Paulo, da Provedoria da Fazenda Real de Santos e as dissertações de ilustrados da época que destacavam a importância do comércio interno para a valorização de regiões do interior do território do Brasil
Keywords: História; Imperialismo - História - Séc. XIX; Portos - Brasil; Santos (SP) - Porto; São Paulo (Estado) - Fronteiras; Brasil - História - Capitanias hereditárias - 1534-1762; Brasil - Comércio exterior; History